Adenomas of the nipple - Gomez Fossati, Carlos; Delgado, Bolivar; Esteían, Alberto; Falconi, Luis; Baldizán, Jorge (Cirugía del Uruguay, 1975)
Nipple adenomas are an uncommon mammary disease. Its interest lies in its possible clínica! confusion with Paget's disease and its possible histopathologic confusion with a ductal carcinoma of a low degree of nalignity. lt is an essentially benign process; which heals with local excision. The authors present 3 cases of his disease developed as erosive costrous lesions of the nipple, of a long-term evolution. Its origm in the sweat glands of the nipple or in the terminal sector of the nipple. ducts is discussed, and the techniques of lo¡al excision of the nipple, necessary for its treatment, are described. The possible consequences of such excision on the underlying mammary gland are analyzed.